Population dynamics of gerres abbreviatus bleeker, 1850 from the parangipettai waters, southeast coast of india - Kuganathan, S. (University of Jaffna, 2006)
The population dynamics of Gerres abbreviatus from the Parangipettai waters, Southeast coast of India was investigated based on length frequency data, using FiSAT software. Growth parameters of G. abbreviatus were estimated using ELEFAN I method. The theoretical ages at length zero (t0) were estimated by substituting the asymptotic length (L∞) and growth coefficient (K) in Pauly’s equation. The fitted von Bertalnaffy’s growth equations for male and femaleG. abbreviatus were Lt=27.8 [1 – exp {-1.30(t+0.1236)}] and Lt=28.2 [1-exp {-1.36 (t+ 0.1175)}] where L∞ values are in cm, K values are on annual basis and t0 values are in years. The estimated growth performance index (Ø) for male and female G. abbreviatus were 3.002 and 3.034 respectively while the estimated life spans of male and female G. abbreviatus were 2.18 and 2.08 years. Instantaneous rates of total mortality (Z) estimated by length converted catch curve for male and female G. abbreviatus were 3.06 and 2.99 yr-1 respectively. Natural mortality (M) estimated by Pauly’s empirical equation for male and female G. abbreviatus were 2.24 and 2.29 yr-1 and the estimated fishing mortality for male and female G. abbreviatus were 0.82 and 0.70 yr-1 respectively. Relative yield per recruit analysis incorporating probabilities of capture indicates that G. abbreviatus in the Parangipettai waters is exploited below the optimum level indicating scope for increase in fishing efforts without leading to overexploitation.